Pleiotropic effects of the COX-2/PGE2 axis in the glioblastoma tumor microenvironment - Dean, Phillip T.; Hooks, Shelley B. (Frontiers in Oncology, 2023)
Glioblastoma (GBM) is the most common and aggressive form of malignant glioma. The GBM tumor microenvironment (TME) is a complex ecosystem of heterogeneous cells and signaling factors. Glioma associated macrophages and microglia (GAMs) constitute a significant portion of the TME, suggesting that their functional attributes play a crucial role in cancer homeostasis. In GBM, an elevated GAM population is associated with poor prognosis and therapeutic resistance. Neoplastic cells recruit these myeloid populations through release of chemoattractant factors and dysregulate their induction of inflammatory programs. GAMs become protumoral advocates through production a variety of cytokines, inflammatory mediators, and growth factors that can drive cancer proliferation, invasion, immune evasion, and angiogenesis. Among these inflammatory factors, cyclooxygenase-2 (COX-2) and its downstream product, prostaglandin E2 (PGE2), are highly enriched in GBM and their overexpression is positively correlated with poor prognosis in patients. Both tumor cells and GAMs have the ability to signal through the COX-2 PGE2 axis and respond in an autocrine/paracrine manner. In the GBM TME, enhanced signaling through the COX-2/PGE2 axis leads to pleotropic effects that impact GAM dynamics and drive tumor progression.